IMPLEMENTASI KEBIJAKAN DINAS PARIWISATA DAN KEBUDAYAAN TENTANG OBJEK WISATA UNGGULAN HAPANASAN - Afrizal, Afrizal; Rusli, Zaili; Yuliani, Febri (Jurnal Ilmu Administrasi Negara, 2019)
Implementation of the Tourism and Culture Office Policy on Hapanasan Leading Tourism Objects. This study aims to determine the implementation of the Tourism and Culture Department’s policy on superior tourism objects hapanasan. Research informants are the head of the tourism department, tourism development staff, community, visitors and tour guards. The sampling technique uses snowball sampling, data collection techniques are carried out by interviews, observation and documentation. Data analysis by using data tringulation. The results show that in the implementation of superior tourism development, hapanasan is still not optimal. There are still many facilities and infrastructures that must be equipped, limited resources, minimal communication and less costs to renovate.